Chronic cerebrospinal venous insufficiency in patients with multiple sclerosis. Issue 4 (5th December 2008) - Zamboni, P; Galeotti, R; Menegatti, E; Malagoni, A M; Tacconi, G; Dall'Ara, S; Bartolomei, I; Salvi, F
Abstract : Background: The extracranial venous outflow routes in clinically defined multiple sclerosis (CDMS) have not previously been investigated. Methods: Sixty-five patients affected by CDMS, and 235 controls composed, respectively, of healthy subjects, healthy subjects older than CDMS patients, patients affected by other neurological diseases and older controls not affected by neurological diseases but scheduled for venography (HAV-C) blindly underwent a combined transcranial and extracranial colour-Doppler high-resolution examination (TCCS-ECD) aimed at detecting at least two of five parameters of anomalous venous outflow. According to the TCCS-ECD screening, patients and HAV-C further underwent selective venography of the azygous and jugular venous system with venous pressure measurement. Results: CDMS and TCCS-ECD venous outflow anomalies were dramatically associated (OR 43, 95% CI 29 to 65, p<0.0001). Subsequently, venography demonstrated in CDMS, and not in controls, the presence of multiple severe extracranial stenosis, affecting the principal cerebrospinal venous segments; this provides a picture of chronic cerebrospinal venous insufficiency (CCSVI) with four different patterns of distribution of stenosis and substitute circle. Moreover, relapsing-remitting and secondary progressive courses were associated with CCSVI patterns significantly different from those of primary progressive (p<0.0001). Finally, the pressure gradient measured across the venous stenosies was slightly but significantly higher. Conclusion: CDMS is strongly associated with CCSVI, a scenario that has not previously been described, characterised by abnormal venous haemodynamics determined by extracranial multiple venous strictures of unknown origin. The location of venous obstructions plays a key role in determining the clinical course of the disease.